Pertempuran Rusia-Uthmaniyah 1877-1878 dan Impaknya terhadap Muslim Bulgaria : The Battle of Russo-Ottoman 1877-1878 and Its Impact on Muslims in Bulgaria - Mat Enh, Azlizan (Journal of Al-Tamaddun, 2024)
The fierce battle that broke out in history between Russia and Ottoman in 1877–1878 was an attempt to solve the problems faced by the Ottoman administration in the Balkans. This is mainly related to accusations that the Ottoman government cannot protect Christians in Bosnia-Herzegovina. Ironically, Russia's victory did not lead to the resolution of the conflict in Bosnia-Herzegovina. Instead, it negatively impacted Muslims in the Balkans, especially in Bulgaria. This article will analyse the social effects of the war on Bulgaria's Muslim minority. This article uses a qualitative method called content analysis to evaluate British official documents and records collected from the British National Archives and the University of London, specifically from the School of Slavonic and East European Studies. The result shows that the Russo-Ottoman War of 1877 was not intended to give justice to the Christian community under the Ottoman empire; on the contrary, it was a strategy used by Russia and the Bulgarian government to eliminate the Muslim minority in Bulgaria.